Preparation method of ultrathin aluminum nitride

The raw materials are fixed by high-temperature tape and the use of four-target closed-field non-equilibrium high-power pulse magnetron sputtering technology, combined with step-by-step thermal annealing process, the problems of thicker aluminum nitride film and prone to crack peeling are solved, and an ultra-thin aluminum nitride film with dense structure and excellent mechanical properties are prepared.

CN119571250APending Publication Date: 2025-03-07FUJIAN HUAQING ELECTRONICS MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411770031.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The aluminum nitride film prepared in the prior art is thicker and prone to cracks and peeling problems.

Method used

High-temperature tape is used to fix raw materials, and unbalanced high-power pulse magnetron sputtering is performed in four-target closed field, combined with step-by-step thermal annealing process to prepare ultra-thin aluminum nitride film.

Benefits of technology

The obtained ultra-thin aluminum nitride film has a dense structure, smooth surface, excellent mechanical properties, effectively inhibiting the cracking and peeling of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571250A_ABST
    Figure CN119571250A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, provides a preparation method of ultrathin aluminum nitride, and solves the problems that an aluminum nitride film prepared in the prior art is relatively thick and is easy to crack and peel off. Comprising the following steps: 1) preparing raw materials: preparing the following raw materials: a pure metal Al target material and a (0001) surface sapphire substrate; 2) pretreatment; 3) loading a sample and vacuumizing; (4) cleaning the chamber and carrying out reverse sputtering; (5) sputtering; and (6) carrying out step-by-step thermal annealing to obtain the ultrathin aluminum nitride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a method for preparing ultra-thin aluminum nitride. Background Art

[0002] Aluminum nitride (AlN), as an important ceramic material, has been widely used in high-tech fields such as electronics, optoelectronics, and aviation due to its excellent physical and chemical properties. In recent years, with the rapid development of the semiconductor industry and materials science, the demand for aluminum nitride materials has increased, especially ultra-thin aluminum nitride films, which have shown great application potential in microelectronic devices, integrated circuit packaging, LED luminescent materials, and high-performance acoustic wave devices. Aluminum nitride films have many unique properties, such as high melting point, high hardness, good chemical stability, excellent electrical insulation and piezoelectric properties. These properties make aluminum nitride films an ideal choice for making high-performance electronic devices, blue and ultraviolet luminescent materials, and GHz-level surface acoustic wave devices. In particular, in surface acoustic wave (SAW) devices, the propagation speed of the surface acoustic wave of aluminum nitride films along the c-axis is as high as 6-6.2km / s, which is much higher than traditional materials such as ZnO, LiTaO3 and LiNbO3. Therefore, the use of aluminum nitride films can significantly increase the center frequency of the device and meet the needs of the development of modern communication technology.

[0003] Chinese patent application No. 201911028132.4 discloses a method for preparing an aluminum nitride single crystal film, an aluminum nitride single crystal film, and a light-emitting diode. The method for preparing an aluminum nitride single crystal film includes providing a substrate, and sequentially generating an aluminum nitride film, an aluminizing layer, and an aluminum nitride epitaxial layer on the substrate. By using this invention, the stability of the crystal can be effectively improved, and the obtained crystal is non-atomized and crack-free, and the crystal quality is high. However, the thickness of the aluminum nitride film of this invention is between 1nm-25nm, which is relatively thick.

[0004] Chinese patent application No. 201810171796.5 discloses a growth method and application of an aluminum nitride film, the growth method comprising the following steps: 1) introducing trimethylaluminum and ammonia to generate a first aluminum nitride layer on a substrate; 2) performing nano-column etching on the first aluminum nitride layer to obtain a columnar recessed aluminum nitride layer, wherein the columnar recessed aluminum nitride layer has a plurality of nano-column recesses; 3) controlling the temperature and pressure of the reaction chamber, introducing trimethylaluminum and ammonia to generate a second aluminum nitride layer on the columnar recessed aluminum nitride layer; 4) controlling the temperature and pressure of the reaction chamber, introducing trimethylaluminum and ammonia to generate a third aluminum nitride layer on the second aluminum nitride layer; wherein the molar flow ratio of ammonia to trimethylaluminum in step 3) is less than the molar flow ratio of ammonia to trimethylaluminum in step 4); the aluminum nitride film is a collection of the first aluminum nitride layer, the second aluminum nitride layer and the third aluminum nitride layer. The present invention can significantly improve the crystal quality of AlN thin films. However, the aluminum nitride film produced by this process is prone to peeling. Summary of the invention

[0005] Therefore, in view of the above problems, the present invention provides a method for preparing ultra-thin aluminum nitride to solve the problem that the aluminum nitride film prepared by the prior art is relatively thick and prone to cracking and peeling.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing ultrathin aluminum nitride comprises the following steps:

[0008] S1. Preparation of raw materials: including the following raw materials: pure metal Al target, (0001) surface sapphire substrate;

[0009] S2, pretreatment: ultrasonically clean the (0001) sapphire substrate in acetone, anhydrous ethanol and deionized water in sequence, and dry it in a N2 atmosphere for later use;

[0010] S3, sample loading and vacuuming: Use high temperature tape to fix the prepared raw materials on the substrate holder, put them into the vacuum chamber, first use a mechanical pump to pump from normal pressure to a vacuum degree of 5-10Pa, start the molecular pump, and make the vacuum degree reach the background vacuum of 2-5×10 -4 Pa;

[0011] S4, chamber cleaning and reverse sputtering: 80sccmAr is introduced for chamber cleaning and target reverse sputtering. A 350V DC pulse power supply is used for chamber cleaning, the working power supply is 2.5Pa, and the cleaning time is 20-30min. Then a 400V high-power modulated pulse power supply is used for target reverse sputtering, the working gas pressure is 0.5Pa, and the pulse discharge parameter τ on / τ offThe discharge frequency is 40 Hz, and the target sputtering time is 10-15 min.

[0012] S5, sputtering: introducing 80sccm of working gas, wherein the working gas is Ar and N2, and the N2 content is 16-25%, adjusting the gate valve to keep the sputtering pressure stable at 0.3-0.5Pa, the discharge voltage is 280-500V, the sputtering power is 1-20kW, and the total pulse length is set to 1000μs, and then the weak ionization stage and the strong ionization stage are entered in sequence. After the sputtering is completed, the sputtering power supply and equipment are turned off according to the prescribed steps, the air inlet valve is opened, and the raw aluminum nitride is obtained;

[0013] S6, step-by-step thermal annealing: the crude aluminum nitride obtained in step S5 is ultrasonically cleaned with acetone, isopropanol, and ethanol in sequence, then blown dry with an air gun, and then placed in a tube furnace, and subjected to primary thermal annealing, secondary thermal annealing, and tertiary thermal annealing in sequence in a normal pressure N2 environment to obtain ultrathin aluminum nitride;

[0014] Wherein, the thickness of the ultra-thin aluminum nitride is 200-1000nm;

[0015] The total pulse length includes a first pulse length in a weak ionization stage and a second pulse length in a strong ionization stage, wherein the second pulse length is ≥400 μs;

[0016] The first thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 850-900°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced; the second thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 800-850°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced; the third thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 700-750°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced.

[0017] Furthermore, the weak ionization stage is: setting the pulse parameter τ on / τ off The peak voltage, peak current and peak power are 390V, 16A and 6.2kW respectively.

[0018] Furthermore, the strong ionization stage is: setting the pulse parameter τ on / τ off The peak voltage, peak current and peak power are 410V, 86A and 35.2kW respectively.

[0019] Furthermore, the purity of Ar and N2 is ≥99.99%.

[0020] Furthermore, the size of the sapphire substrate is 2 inches.

[0021] Furthermore, the ultrasonic cleaning is carried out in an ultrasonic homogenizer with an ultrasonic power of 300-400W and an ultrasonic time of 10-15min.

[0022] By adopting the above technical solution, the beneficial effects of the present invention are:

[0023] 1. When the degree of N2 ionization is low, the deposited AlN film is in the Al state. At the same time, a large number of unionized N2 molecules collide with Ar atoms, which will reduce the free path and the kinetic energy of the sputtered atoms, resulting in poor crystal quality of the AlN film. Therefore, it is necessary to increase the N2 ionization rate. Through the method of high-power modulated pulse magnetron sputtering, plasma is generated in the weak ionization stage of the entire pulse, maintaining a relatively stable discharge power and discharge current, and then the ionization is increased through the strong ionization stage to obtain a highly ionized plasma. First, in the weak ionization stage, the plasma is ignited by a low micropulse duty cycle, and then the duty cycle is increased in the strong ionization stage to obtain a highly ionized discharge current, thereby increasing the ionization rate of N2, thereby depositing an ultra-thin (002) preferentially oriented AlN film on a sapphire substrate; at the same time, by adjusting the on and off time of the pulse discharge, a stable deposition process can be achieved, and the deposited AlN film has a dense structure, a smooth surface, and excellent mechanical properties.

[0024] 2. Step-by-step thermal annealing has an extremely fast temperature change rate, including heating and cooling. During the rapid thermal annealing process, grain recrystallization and grain merging occur, which reduces the grain boundaries of the film, thereby reducing screw dislocations. The interface between the AlN film and the sapphire substrate becomes clear, and there is no thin buffer layer near the interface. Therefore, rapid thermal annealing has a good release effect on the residual stress of the sputtered AlN film, thereby effectively inhibiting the cracking and peeling of the AlN film. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of a four-target closed-field unbalanced high-power pulsed magnetron sputtering system in Examples 1 to 3 of the present invention;

[0026] Figure 2 Schematic diagram of the three-dimensional structure of (002) preferentially oriented aluminum nitride in Examples 1 to 3 of the present invention;

[0027] Explanation of the numbers in the figure: 1-vacuum chamber, 2-magnetron sputtering target, 3-sputtering power supply. DETAILED DESCRIPTION

[0028] Example 1

[0029] refer to Figure 1 to Figure 2 , a method for preparing ultrathin aluminum nitride, comprising the following steps:

[0030] S1. Preparation of raw materials

[0031] The material includes the following: a pure metal Al target material, and a 2-inch (0001) sapphire substrate, wherein the crystal structure of sapphire (Al2O3) is a hexagonal lattice structure, and the 0001 (C surface) is its natural growth surface, which has lower surface energy and better thermal conductivity;

[0032] S2. Preprocessing

[0033] The (0001) surface sapphire substrate was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in sequence, wherein the ultrasonic cleaning was performed in an ultrasonic homogenizer with an ultrasonic power of 300 W and an ultrasonic time of 10 min, and then dried in a N2 atmosphere for later use;

[0034] S3. Sample loading and vacuuming

[0035] Use high-temperature tape to fix the prepared raw material on the substrate holder and put it into the vacuum chamber 1. First, use a mechanical pump to pump from normal pressure to a vacuum degree of 5 Pa, and start the molecular pump to make the vacuum degree reach a background vacuum of 2×10 -4 Pa;

[0036] S4, chamber cleaning and back sputtering

[0037] The sputtering is carried out in a four-target closed-field unbalanced high-power pulsed magnetron sputtering system 1, which comprises: a vacuum chamber 1, four magnetron sputtering targets 2 and four sputtering power supplies 3. First, 80 sccm Ar is introduced for chamber cleaning and target back-sputtering. A 350V DC pulse power supply is used for chamber cleaning, the working power supply is 2.5Pa, and the cleaning time is 20min. Then, a 400V high-power modulated pulse power supply is used for target back-sputtering, the working gas pressure is 0.5Pa, and the pulse discharge parameter τ on / τ off is 6μs / 34μs, the discharge frequency is 40Hz, and the sputtering target time is 10min;

[0038] S5, Sputtering

[0039] 80 sccm of working gas was introduced, the working gas was Ar and N2, the purity of Ar and N2 were both ≥99.99%, the N2 content was 16.7%, the gate valve was adjusted to keep the sputtering pressure stable at 0.3 Pa, the discharge voltage was 280 V, the sputtering power was 1 kW, the total pulse length was set to 1000 μs, and then the weak ionization stage and the strong ionization stage were entered in sequence. The weak ionization stage was: the pulse parameter τ was set on / τ offThe peak voltage, peak current and peak power are 390V, 16A and 6.2kW respectively; the strong ionization stage is as follows: setting the pulse parameter τ on / τ off The time duration is 6μs / 10μs, and the peak voltage, peak current and peak power are 410V, 86A and 35.2kW respectively. After the sputtering is completed, the sputtering power supply and equipment are turned off according to the prescribed steps, the air inlet valve is opened, and the raw aluminum nitride is taken out to obtain the raw aluminum nitride.

[0040] S6, step-by-step thermal annealing

[0041] The crude aluminum nitride obtained in step S5 is ultrasonically cleaned with acetone, isopropanol, and ethanol in sequence, then blown dry with an air gun, and then placed in a tube furnace, and subjected to a first thermal annealing, a second thermal annealing, and a third thermal annealing in sequence in a normal pressure N2 environment to obtain an ultra-thin (002) preferentially oriented aluminum nitride with a thickness of 200 nm;

[0042] like Figure 2 , the c-axis direction is the polar axis direction of aluminum nitride. When mechanical force is applied along this direction, the strongest charge will be generated on the (002) plane. When mechanical force is applied along the a-axis direction perpendicular to the polar axis, no charge will be generated on the (100) plane, but charge will still be generated on the (002) plane. Therefore, the c-axis direction is the direction with the strongest piezoelectric performance of aluminum nitride.

[0043] The total pulse length includes a first pulse length in a weak ionization stage and a second pulse length in a strong ionization stage, wherein the first pulse length is 600 μs and the second pulse length is 400 μs.

[0044] The first thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 850°C, kept warm for 3 minutes, and the temperature is naturally reduced; the second thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 800°C, kept warm for 3 minutes, and the temperature is naturally reduced; the third thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 700°C, kept warm for 3 minutes, and the temperature is naturally reduced.

[0045] Example 2

[0046] A method for preparing ultrathin aluminum nitride comprises the following steps:

[0047] S1. Preparation of raw materials

[0048] The material includes the following: a pure metal Al target material, and a 2-inch (0001) sapphire substrate, wherein the crystal structure of sapphire (Al2O3) is a hexagonal lattice structure, and the 0001 (C surface) is its natural growth surface, which has lower surface energy and better thermal conductivity;

[0049] S2. Preprocessing

[0050] The (0001) surface sapphire substrate was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning was carried out in an ultrasonic homogenizer, the ultrasonic power was 350 W, the ultrasonic time was 12 min, and then dried in a N2 atmosphere for later use;

[0051] S3. Sample loading and vacuuming

[0052] Use high-temperature tape to fix the prepared raw material on the substrate holder and put it into the vacuum chamber 1. First, use a mechanical pump to pump from normal pressure to a vacuum degree of 8 Pa, and start the molecular pump to make the vacuum degree reach a background vacuum of 3×10 -4 Pa;

[0053] S4, chamber cleaning and back sputtering

[0054] The sputtering is carried out in a four-target closed-field unbalanced high-power pulsed magnetron sputtering system 1, which comprises: a vacuum chamber 1, four magnetron sputtering targets 2 and four sputtering power supplies 3. First, 80 sccm Ar is introduced for chamber cleaning and target back-sputtering. A 350V DC pulse power supply is used for chamber cleaning, the working power supply is 2.5Pa, and the cleaning time is 25min. Then, a 400V high-power modulated pulse power supply is used for target back-sputtering, the working gas pressure is 0.5Pa, and the pulse discharge parameter τ on / τ off is 6μs / 34μs, the discharge frequency is 40Hz, and the sputtering target time is 12min;

[0055] S5, Sputtering

[0056] 80 sccm of working gas was introduced, the working gas was Ar and N2, the purity of Ar and N2 were both ≥99.99%, the N2 content was 20%, the gate valve was adjusted to keep the sputtering pressure stable at 0.4 Pa, the discharge voltage was 350 V, the sputtering power was 8 kW, the total pulse length was set to 1000 μs, and then the weak ionization stage and the strong ionization stage were entered in turn. The weak ionization stage was: the pulse parameter τ was set on / τ off The peak voltage, peak current and peak power are 390V, 16A and 6.2kW respectively; the strong ionization stage is as follows: setting the pulse parameter τ on / τ off The time duration is 6μs / 10μs, and the peak voltage, peak current and peak power are 410V, 86A and 35.2kW respectively. After the sputtering is completed, the sputtering power supply and equipment are turned off according to the prescribed steps, the air inlet valve is opened, and the raw aluminum nitride is taken out to obtain the raw aluminum nitride.

[0057] S6, step-by-step thermal annealing

[0058] The crude aluminum nitride obtained in step S5 is ultrasonically cleaned with acetone, isopropanol, and ethanol in sequence, then blown dry with an air gun, and then placed in a tube furnace, and subjected to a first thermal annealing, a second thermal annealing, and a third thermal annealing in sequence in a normal pressure N2 environment to obtain an ultra-thin aluminum nitride with a thickness of 200 nm;

[0059] The total pulse length includes a first pulse length in a weak ionization stage and a second pulse length in a strong ionization stage, wherein the first pulse length is 600 μs and the second pulse length is 400 μs.

[0060] The first thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 880°C, kept at this temperature for 4 minutes, and the temperature is naturally reduced; the second thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 820°C, kept at this temperature for 4 minutes, and the temperature is naturally reduced; the third thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 720°C, kept at this temperature for 4 minutes, and the temperature is naturally reduced.

[0061] Example 3

[0062] A method for preparing ultrathin aluminum nitride comprises the following steps:

[0063] S1. Preparation of raw materials

[0064] The material includes the following: a pure metal Al target material, and a 2-inch (0001) sapphire substrate, wherein the crystal structure of sapphire (Al2O3) is a hexagonal lattice structure, and the 0001 (C surface) is its natural growth surface, which has lower surface energy and better thermal conductivity;

[0065] S2. Preprocessing

[0066] The (0001) surface sapphire substrate was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water in sequence, wherein the ultrasonic cleaning was performed in an ultrasonic homogenizer with an ultrasonic power of 400 W and an ultrasonic time of 15 min, and then dried in a N2 atmosphere for later use;

[0067] S3. Sample loading and vacuuming

[0068] Use high-temperature tape to fix the prepared raw material on the substrate holder and put it into the vacuum chamber 1. First, use a mechanical pump to pump from normal pressure to a vacuum degree of 10Pa, and start the molecular pump to make the vacuum degree reach the background vacuum of 5×10 -4 Pa;

[0069] S4, chamber cleaning and back sputtering

[0070] The sputtering is carried out in a four-target closed-field unbalanced high-power pulsed magnetron sputtering system 1, which comprises: a vacuum chamber 1, four magnetron sputtering targets 2 and four sputtering power supplies 3. First, 80 sccm Ar is introduced for chamber cleaning and target back-sputtering. A 350V DC pulse power supply is used for chamber cleaning, the working power supply is 2.5Pa, and the cleaning time is 30min. Then, a 400V high-power modulated pulse power supply is used for target back-sputtering, the working gas pressure is 0.5Pa, and the pulse discharge parameter τ on / τ off is 6μs / 34μs, the discharge frequency is 40Hz, and the sputtering target time is 15min;

[0071] S5, Sputtering

[0072] 80 sccm of working gas was introduced, the working gas was Ar and N2, the purity of Ar and N2 were both ≥99.99%, the N2 content was 25%, the gate valve was adjusted to keep the sputtering pressure stable at 0.5 Pa, the discharge voltage was 500 V, the sputtering power was 20 kW, the total pulse length was set to 1000 μs, and then the weak ionization stage and the strong ionization stage were entered in sequence. The weak ionization stage was: the pulse parameter τ was set on / τ off The peak voltage, peak current and peak power are 390V, 16A and 6.2kW respectively; the strong ionization stage is as follows: setting the pulse parameter τ on / τ off The time duration is 6μs / 10μs, and the peak voltage, peak current and peak power are 410V, 86A and 35.2kW respectively. After the sputtering is completed, the sputtering power supply and equipment are turned off according to the prescribed steps, the air inlet valve is opened, and the raw aluminum nitride is taken out to obtain the raw aluminum nitride.

[0073] S6, step-by-step thermal annealing

[0074] The crude aluminum nitride obtained in step S5 is ultrasonically cleaned with acetone, isopropanol, and ethanol in sequence, then blown dry with an air gun, and then placed in a tube furnace, and subjected to a first thermal annealing, a second thermal annealing, and a third thermal annealing in sequence in a normal pressure N2 environment to obtain an ultra-thin aluminum nitride with a thickness of 200 nm;

[0075] The total pulse length includes a first pulse length in a weak ionization stage and a second pulse length in a strong ionization stage, wherein the first pulse length is 600 μs and the second pulse length is 400 μs.

[0076] The first thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 900°C, kept at this temperature for 5 minutes, and the temperature is naturally reduced; the second thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 850°C, kept at this temperature for 5 minutes, and the temperature is naturally reduced; the third thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 750°C, kept at this temperature for 5 minutes, and the temperature is naturally reduced.

[0077] Comparative Example 1

[0078] The method for growing an aluminum nitride film comprises the following steps:

[0079] Aluminum nitride is deposited on a (0001) surface sapphire substrate, and the aluminum nitride is baked. The aluminum nitride is deposited in a mixed gas environment of argon and nitrogen, the deposition environment temperature is 550°C, the deposition thickness is 1300nm, the volume of argon and nitrogen is 0.2, and 0.02 volume ratio of oxygen is added to the mixed gas of argon and nitrogen to obtain crude aluminum nitride. The difference from Example 1 is that the annealing adopts a conventional thermal annealing process, specifically, the obtained crude aluminum nitride is ultrasonically cleaned with acetone, isopropanol, and ethanol in turn, then blown dry with an air gun, and then placed in a tubular furnace, the thermal annealing temperature is set to 900°C, the heating rate is 15°C / min, the holding time is 5min, and then the temperature is naturally lowered to obtain an aluminum nitride film.

[0080] The product test data obtained from Example 1, Example 2, Example 3 and Comparative Example 1 are shown in Table 1.

[0081] Table 1

[0082]

[0083] AlN piezoelectric films have excellent physical and chemical properties, such as high sound velocity, high thermal conductivity, large dielectric constant, low high-frequency loss, good piezoelectric performance, good chemical stability, etc., so they are widely used in surface acoustic wave and bulk acoustic wave devices. In acoustic wave resonators, AlN films are required to have a high degree of c-axis orientation, high film flatness, and excellent piezoelectric properties, where the c-axis orientation can also be expressed as (002) preferred orientation. Therefore, in order to meet the above requirements, it is necessary to improve the crystal orientation and surface roughness of the film.

[0084] As can be seen from Table 1, the surface thickness of the film of the products of Example 1, Example 2 and Example 3 is relatively thin, and the surface roughness is up to 0.39nm, indicating that the surface of the product prepared by this technical solution is dense and has good flatness. The growth direction shows that the product film has a c-axis preferred orientation. The tensile stress of the products of Example 1, Example 2 and Example 3 is lower than 0.96GPa, and the tensile stress of the comparative product is 1.1GPa, indicating that the thermal annealing process of this technical solution can better release stress and avoid the shedding of the film.

[0085] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A method for preparing ultrathin aluminum nitride, characterized in that: The following steps are involved: S1. Preparation of raw materials: The raw materials include: pure metal Al target, (0001) surface sapphire substrate; S2, pretreatment: ultrasonically clean the (0001) sapphire substrate in acetone, anhydrous ethanol and deionized water in sequence, and dry it in a N2 atmosphere for later use; S3, sample loading and vacuuming: Use high temperature tape to fix the prepared raw materials on the substrate holder, put them into the vacuum chamber, first use a mechanical pump to pump from normal pressure to a vacuum degree of 5-10Pa, start the molecular pump, and make the vacuum degree reach the background vacuum of 2-5×10 -4 Pa; S4, chamber cleaning and reverse sputtering: 80sccmAr is introduced for chamber cleaning and target reverse sputtering. A 350V DC pulse power supply is used for chamber cleaning, the working power supply is 2.5Pa, and the cleaning time is 20-30min. Then a 400V high-power modulated pulse power supply is used for target reverse sputtering, the working gas pressure is 0.5Pa, and the pulse discharge parameter τ on / τ off The discharge frequency is 40 Hz, and the target sputtering time is 10-15 min. S5, sputtering: introducing 80sccm of working gas, wherein the working gas is Ar and N2, and the N2 content is 16-25%, adjusting the gate valve to keep the sputtering pressure stable at 0.3-0.5Pa, the discharge voltage is 280-500V, the sputtering power is 1-20kW, and the total pulse length is set to 1000μs, and then the weak ionization stage and the strong ionization stage are entered in sequence. After the sputtering is completed, the sputtering power supply and equipment are turned off according to the prescribed steps, the air inlet valve is opened, and the raw aluminum nitride is obtained; S6, step-by-step thermal annealing: the crude aluminum nitride obtained in step S5 is ultrasonically cleaned with acetone, isopropanol, and ethanol in sequence, then blown dry with an air gun, and then placed in a tube furnace, and subjected to primary thermal annealing, secondary thermal annealing, and tertiary thermal annealing in a normal pressure N2 environment in sequence to obtain ultrathin aluminum nitride; Wherein, the thickness of the ultra-thin aluminum nitride is 200-1000nm; The total pulse length includes a first pulse length in a weak ionization stage and a second pulse length in a strong ionization stage, wherein the second pulse length is ≥400 μs; The first thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 850-900°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced; the second thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 800-850°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced; the third thermal annealing is as follows: the heating rate is 40°C / s, the temperature is raised to 700-750°C, the temperature is kept for 3-5 minutes, and the temperature is naturally reduced.

2. The method for preparing ultrathin aluminum nitride according to claim 1, characterized in that: The weak ionization stage is: setting the pulse parameter τ on / τ off The peak voltage, peak current and peak power are 390V, 16A and 6.2kW respectively.

3. The method for preparing ultrathin aluminum nitride according to claim 1, characterized in that: The strong ionization stage is: setting the pulse parameter τ on / τ off The peak voltage, peak current and peak power are 410V, 86A and 35.2kW respectively.

4. The method for preparing ultrathin aluminum nitride according to claim 1, characterized in that: The purity of Ar and N2 is both ≥99.99%.

5. The method for preparing ultrathin aluminum nitride according to claim 1, characterized in that: The size of the sapphire substrate is 2 inches.

6. The method for preparing ultrathin aluminum nitride according to claim 1, characterized in that: The ultrasonic cleaning is carried out in an ultrasonic homogenizer with an ultrasonic power of 300-400W and an ultrasonic time of 10-15min.

Citation Information

Patent Citations

  • A method for growing aluminum nitride films and their applications

    CN108538968B

  • Aluminum nitride single crystal film preparation method, aluminum nitride single crystal film and light emitting diode

    CN112725896A